Lessons Learned From the Higher Risk Perception and the Efficient Flood Mitigation in Haji-Abad, Golestan Province, Iran, 2019. (13th June 2021) - Heidari, Mohammad; Sayfouri, Nasrin; Heidari, Samaneh
ABSTRACT: Objective: In the present study, the factors inducing the successful immediate mitigation measures and other activities at Haji-Abad village in Golestan Province, Iran, were scrutinized. Methods: To find authentic data, information was gathered from a variety of sources, including mass media documents and interviews with the related Health House attendant (Behvarz) at Haji-Abad and the disaster liaison at the Rural-Urban Healthcare Center, both of whom were among the residents. A thematic analysis was performed on the transcriptions. Results: The findings showed that apart from the favorable geographical location of the area, appropriate education as well as vast family kinship among the residents were the major causes that induced high-risk perception, adequate collaboration and coordination among the residents and between them and the local authorities, and the women's active participation; these major effects, in turn, helped provide all of the efficient mitigation measures leading to the flood control. Conclusion: It is recommended that opportunities for people's collaboration in preparedness, mitigation measures, and resilience during the occurrence of disasters be arranged by means of providing related inclusive operational education prior to the incidents. This can simultaneously generate risk perception and help people assume themselves as the owners of the disasters.